Global Sourcing under Imperfect Capital Markets - Carluccio, Juan; Fally, Thibault (The Review of Economics and Statistics, 2012)
We develop a simple model to study the interactions between a supplier's financial constraints and contract incompleteness in a vertical relationship. Applied to the analysis of multinational firms' sourcing strategies, the model predicts: (i) that complex and specific inputs are more likely to be sourced from financially developed countries and (ii) that multinationals are more likely to integrate suppliers located in countries with poor financial institutions, especially when trade involves complex goods. These predictions are examined and validated using firm-level trade data on multinational firms with operations in France.